Mineralogical and petrographic characterisation of flake graphite in the graphite mica schist rocks from the Nubian Desert, Sudan - Desouqi, Dalal; Mohd Salleh, Mohamad Amran; Roselee, Muhammad Hatta; M. Yahya, Aisyah; Alsalam, Bushra Abdo; Abdul Rashid, Suraya (Elsevier B.V., 2025)
The Nubian Desert in Sudan, spanning from the Nile River in Wadi Halfa to the eastern Red Sea region, hosts graphite-bearing rocks that can potentially meet the increasing demand for natural graphite, a critical mineral in green energy technologies. This study is the first to investigate the detailed mineralogical and petrographic characteristics of graphite-bearing rocks from this region using petrography, scanning electron microscopy (SEM), energy-dispersive X-ray spectrometry (EDX), X-ray diffraction (XRD), and thermogravimetric analysis (TGA). The Nubian Desert flake graphite is of high-grade and hosted in metamorphic graphite schist that has been subjected to an increasing regional environment of amphibolite-to-greenschist facies. The schist is of high-grade and fine-grained, with a clear foliation texture composed of graphite (10 %), quartz (35 %), mica (biotite+muscovite) (50 %), and albite (5 %). Fine graphite flakes, ranging from 50 to 150 µm in length with an average width of 46 µm, are disseminated along the schist foliation texture. The quantitative elemental contents are C (10 %), SiO2 (60 %), Al₂O₃ (20 %), and K₂O (10 %). Approximately 84 % of the total carbon is graphite, whereas 16 % is graphitised carbon, which can be upgraded by froth flotation and acid leaching. Although the crystallinity and microcrystal structure of the graphite require further investigation, the preliminary mineralogical features meet the international standards for high-grade fine-flake graphite and suggest its suitability for advanced processing and exploration. These findings highlight the Nubian Desert as an important and underexplored graphite resource, necessitating expanded geological and industrial investigations to meet the growing demand for critical minerals required for sustainable energy technologies.